Passengers on barge being towed aboard S.S. VICTORIA from the beach, Nome, September 14, 1904 - Nowell, Frank H., 1864-1950 (1904)
Caption on image: Passengers being Towed Aboard "S.S. Victoria" through Heavy Surf. Nome, Sept. 14th 04. Nowell 1904. 1118 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number